Ayurvedic Management of Kampavata - V. Gowthami; G. Sree Devi; A. Swaroopa; P. Srikanth Babu (AYUSHDHARA, 2024)
Kampavata is one among Vataja nanatmaja vyadhis. Acharya Charaka, Susrutha, Vagbhata, Madhavakara, Kashyapa mentioned Kampavata as Vepathu. It can be correlated with “Tremors” in modern science which is the most common movement disorder. The total number of people suffering from ET worldwide was 24.91 million in 2020 and incidence increases with age. Kampa is the prominent feature in Kampavata which is categorized as Sarvanga-kampa and Shiro-kampa. Kampa occurs due to Prakopa of Chalaguna which is the inherent quality of Vata dosha. The management of essential tremors in the conventional system of medicine is decreasing quality of life of patient with certain side effects like fatigue, impotence, bradycardia, reduced blood pressure, drowsiness, nausea, dizziness, ataxia, confusion, vertigo, paresthesia etc. By Ayurvedic intervention patient quality of life can be preserved. In the present clinical study patient was treated with Snehana and Brmhana line of management in the form of Shirodhara, Nasya and Samana oushadies like Sarvamayantakaghrta etc. The outcome of the study revealed good therapeutic efficacy and patient got remarkable relief in symptoms, that are assessed by TRG Essential tremor rating assessment scale (TETRAS©) V 3.1.